Discurso, conocimiento social e identidad en un grupo de iguales gitano - Poveda, David P. (Revista de Antropología Social, 2007)
This article examines the way in which a group of Gypsy children talks in their spontaneous interactions about different sets of residents of their neighborhood. The data is part of a linguistic ethnography of peer interactions of a group of Gypsy children from a mid-sized Spanish city and this article focuses on a ‘night stroll’ the children took in which they moved away from their habitual play areas and walked through different parts of their district. The neighborhood is relatively heterogeneous in socio-economic and ethnic terms as a result of several social and urban transformations. Two discursive mechanisms, membership categorization and stylization, are examined to show the role talk plays in children’s understanding of this social heterogeneity in relation to their own ethnic and social identity. Finally, the article points out some of the potentials of ethnographic microanalysis of social interaction to study children’s social knowledge in action.